In vivo investigation of Lcr35® anti-candidiasis properties in Caenorhabditis elegans reveals the involvement of highly conserved immune pathways - Poupet, Cyril; Rifa, Étienne; Theil, Sébastien; Bonnet, Muriel; Veisseire, Philippe; Cardin, Guillaume; Guéret, Élise; Rialle, Stéphanie; Chassard, Christophe; Nivoliez, Adrien; Bornes, Stéphanie (Frontiers in Microbiology, 2022)
Lactic acid bacteria, including the microorganisms formerly designated as Lactobacillus, are the major representatives of Live Biotherapeutic Microorganisms (LBM) when used for therapeutic purposes. However, in most cases, the mechanisms of action remain unknown. The antifungal potential of LBM has already been demonstrated using preclinical models (cell cultures, laboratory animals). Understanding their mechanisms of action is strategic for the development of new therapeutics for humans. Here, Caenorhabditis elegans was used as an in vivo model to analyze pro-longevity, anti-aging and anti-candidiasis effects of the LBM Lacticaseibacillus rhamnosus (formerly Lactobacillus rhamnosus) Lcr35®. A high-throughput transcriptomic analysis revealed a specific response of C. elegans depending on whether it is in the presence of the LBM L. rhamnosus Lcr35® (structural response), the yeast Candida albicans (metabolic response) or both (structural and metabolic responses) in a preventive and a curative conditions. Studies on C. elegans mutants demonstrated that the p38 MAPK (sek-1, skn-1) and the insulin-like (daf-2, daf-16) signaling pathways were involved in the extended lifespan provided by L. rhamnosus Lcr35® strain whereas the JNK pathway was not involved (jnk-1). In addition, the anti C. albicans effect of the bacterium requires the daf-16 and sek-1 genes while it is independent of daf-2 and skn-1. Moreover, the anti-aging effect of Lcr35®, linked to the extension of longevity, is not due to protection against oxidative stress (H2O2). Taken together, these results formally show the involvement of the p38 MAP kinase and insulin-like signaling pathways for the longevity extension and anti-Candida albicans properties of Lcr35® with, however, differences in the genes involved. Overall, these findings provide new insight for understanding the mechanisms of action of a probiotic strain with antimicrobial potential.